กระบวนการพิจารณารายงานการวิเคราะห์ผลกระทบสิ่งแวดล้อมประเภทโครงการอาคารอยู่อาศัยรวม ตามกฎหมายว่าด้วยการควบคุมอาคาร - ฐาปณีย์ พันธุ์เพชร (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
As the destruction of the environment is one of the most important problems affecting the country, the Thai government needs to take legal measures to deal with it. Environmental impact assessment is a tool in the field of natural resource and environmental management under the Enhancement and Conservation of National Environmental Quality Act, B.E. 1992 (NEQA 1992) requires that owners of building development projects including unity housing projects with over 80 units under the Building Control Act submit reports about the environmental impact of their projects. In this regard, it was found that, as there are a high number of unity housing development projects, the assessment process of the reports about the environmental impact have been delayed. The research focuses on studying the unity housing project report assessment process and related problems. The reports of the meeting of the Assessment Specialist Committee, the reports of the unity housing projects, research reviews and related documents were analyzed and studied. Moreover, those who are involved with the assessment project, namely the Assessment Committee, the officers from the Policy and Plan for the Natural Resources and Environment, the environmental impact reporters, etc., were interviewed. The study was conducted over a period of one year, starting from July 2006 to June 2007. From the studies, it was found that there were 55 meetings held to consider 248 issues or 130 projects consisting of not-over- 23 –meter- high unity housing projects and 41 of the 23- meter- or- over high rise buildings. Of these, 70 projects passed the assessment. Initially, 6 project reports were approved while the rest were returned to be revised from one to five times. The fastest report consideration took 50 days while the longest one took 876 days. Report consideration took an average of 193.4 days or 6 to 7 months while it is specified in the related Act to take not more than 75 days. The delay was due to revisions of the reports regarding the issues of traffic, fire prevention measures, economic and social conditions, green areas, land use, waste management, aesthetics, sewer system, waste water treatment, use of water, light shading and detailed information about the projects in question. It was also found that the project reports were revised several times, which resulted in a delay of the consideration. This correlates with the previous research. Moreover, the delayed and time-consuming consideration process was found in the project reports of the 23-meter-or-more high-rise buildings in the cities, which have a much more serious impact on the environment than the not-over-23-meter-high buildings in the same area.